Intermittent Regional Therapy with rt-PA is not Superior to Systemic Thrombolysis in Deep Vein Thrombosis (DVT) - a German Multicenter Trial - Schwieder, G; Grimm, W; Siemens, H J; Flor, B; Hilden, A; Gmelin, E; Friedrich, H J; Wagner, T (Thrombosis and Haemostasis, 1995)
In a prospective and randomized multicenter trial the efficacy of intermittent regional and systemic thrombolytic therapy for DVT was evaluated. 137 patients with phlebographically confirmed acute DVT above the calf region were treated with 20 mg of rt-PA for 4 h each day. Thrombolysis was applied either locally via a dorsal pedal vein of the firmly bandaged affected leg or systemically using a cubital vein. Treatment lasted for 4-7 days, and during this time unfractionated heparin was applied continuously with the dosage adjusted according to aPTT (1.5-2.0 times the normal value). A second phlebography was performed within 24 h after the end of treatment. Results were evaluated by an independent radiologist who was unaware of the treatment givenSignificant thrombolytic results (e.g. lysis of more than 50% of the original thrombus and complete recanalization of all affected veins) were reached in only 1/3 of all patients. Rates of recanalization did not differ in both groups and bleeding complications occurred in 26.5%. We conclude that intermittent local or systemic application of 20 mg rt-PA seems to be ineffective in the treatment of DVT